A Re-reading of Pitirim SorokinвЂ™s Sociology: To Commemorate The Publication of Thirteen Volumes of his Collected Works - Nikolay A. Golovin (Социологический журнал)
This 30-volume edition of the Collected Works of Russian-American sociologist Pitirim Aleksandrovich Sorokin (1889–1968), the publication of which is ongoing with support from the Komi Republic Government (Russian Federation), is unique and the most extensive in Russian sociology. The review article critically assesses the preparation for publication of 13 volumes that cover almost the entire Russian period of the sociologist’s work. The introductory articles to the volumes not only introduce him to the reader, but also collectively provide an overview of the classic sociologist’s scientific program and the stages of its implementation. Carefully selected by the publishers, reviews of P.A. Sorokin’s books by his contemporaries, attached to the volumes of the Collected Works, and an excellent scientific and reference apparatus (indexes of names and cited literature) allow us to reconstruct the historical and scientific context of P.A. Sorokin’s theoretical and methodological thought, with a few exceptions regarding the racial theories that penetrated sociology in the late 19th and early 20th centuries. Controversial terminological solutions in translating the conceptual apparatus from English into Russian were examined. Today P.A. Sorokin’s landmark studies need to be reconsidered through a new lens and reevaluated given how much time has passed and that the current historical situation in our country and in the world is no less complicated than the period during which his work was created. As such, the points of accession to P.A. Sorokin’s ideas, primarily in the theory and methodology of sociology, have been identified: his underestimated contribution to the development of the General Theory of Social Systems and the Methodology of the Study of Value Systems in the dynamics of society.